MUTU SENSORI MI INSTAN BERBAHAN PATI SAGU TERMODIFIKASI DAN IKAN PATIN - Resy Fressetya; Yusmarini Yusmarini; Vonny Setiaries Johan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The objectives of this research were to get microbiologically modified sago starch by using Lactobacillus plantarum 1 RN2-53 and to get the best formulation that meets the Indonesian Instant Noodle Standard (SNI 01- 3551- 2000). The aims of catfish meat added was to increase integrities and protein content of instant noodles. The design used in this study was Completely Randomized Design with six treatments and three replications. The treatment in this research included SP0 (nature sago starch 100%), SP1 (mosas 100%), SP2 (mosas 97.5%, catfish meat 2.5%), SP3 (mosas 95%, catfish meat 5%), SP4 (92.5%, catfish meat 7.5%) and SP5 (mosas 90%, catfish meat 10%). The data obtained were statistically analyzed using Analysis of Variance (ANOVA) and followed by a test using Duncan’s New Multiple Range Test (DNMRT) at the level of 5%. The best formulation instant noodles was SP3 with ratio mosas 95% and catfish 5%. The result of analysis showed that the ratio of mosas and catfish meat significanly affected organoleptic test of colour, texture, catfish flavor before and after rehydration and mosas flavor before rehydration but did not significantly influence taste of mosas, taste of catfish and mosas flavor after rehydration, whille the hedonic test assessed according to the likes of panelist.Keywords: instant noodles, modified sago starch (mosas), Lactobacillus plantarum, catfish, sensory quality.